Towards Real-Time Semantics for a Distributed Event-Based MOP Language - Sanabria, Mateo; Garzón Alfonso, Wilmer; Benavides Navarro, Luis Daniel (Springer Nature, 2018)
This paper investigates rewriting logic as a suitable means to model the semantics of distributed and concurrent systems implemented using Monitoring Oriented Programming (MOP) frameworks. MOP tools close the gap between specification and implementation, allowing several formal specifications and concrete implementations to be combined into a single executing system. To address real-time monitoring of modern distributed applications, we recently proposed REAL-T, a reactive event-based distributed programming language with explicit support for distributions and time manipulation. REAL-T allows programmers to instrument distributed applications to monitor and enforce specific behavior. It also supports requirements of modern reactive applications (responsiveness, resiliency, elasticity and asynchronous communication). The REAL-T programming model is very flexible, making the semantic specifications very challenging.

Este artículo investiga la lógica de reescritura como un medio adecuado para modelar la semántica de sistemas distribuidos y concurrentes implementados utilizando marcos de Programación Orientada a Monitoreo (MOP). Las herramientas MOP cierran la brecha entre la especificación y la implementación, lo que permite combinar varias especificaciones formales e implementaciones concretas en un solo sistema de ejecución. Para abordar el monitoreo en tiempo real de las aplicaciones distribuidas modernas, recientemente propusimos REAL-T, un lenguaje de programación distribuido basado en eventos reactivos con soporte explícito para distribuciones y manipulación del tiempo. REAL-T permite a los programadores instrumentar aplicaciones distribuidas para monitorear y hacer cumplir un comportamiento específico. También es compatible con los requisitos de las aplicaciones reactivas modernas (capacidad de respuesta, resiliencia, elasticidad y comunicación asíncrona). El modelo de programación REAL-T es muy flexible, lo que hace que las especificaciones semánticas sean muy desafiantes.
Keywords: Semántica de sistemas; Reestructura lógica; Programación orientada a eventos; REAL-T; Lenguaje de programación; Rewriting logic; Semantics; Distributed programming; Event oriented programming; Explicit time management